2021
DOI: 10.21037/atm-20-1353
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms based on clinicopathological factors and inflammatory indicators for prediction of early and late recurrence of hepatocellular carcinoma after surgical resection for patients with chronic hepatitis B

Abstract: Background: Few studies have focused on the prognostic values of inflammation-related factors for different phases of recurrence in hepatocellular carcinoma (HCC). We aimed to identify the different risk factors for overall, early, and late recurrence, and to establish nomograms based on inflammation-related parameters for predicting the risks of recurrence in a group of HCC patients undergoing hepatectomy.Methods: We retrospectively enrolled 383 HCC patients with chronic hepatitis B (CHB) who underwent hepate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The satellite nodule was an independent risk factor for recurrence within 1 year following surgery (31). Studies have shown that the tumor number correlated with the recurrence of huge HCC (32,33). Xia et al (34) also reported that age was an independent risk factor for HCC early recurrence within 1 year of curative hepatectomy.…”
Section: Discussionmentioning
confidence: 98%
“…The satellite nodule was an independent risk factor for recurrence within 1 year following surgery (31). Studies have shown that the tumor number correlated with the recurrence of huge HCC (32,33). Xia et al (34) also reported that age was an independent risk factor for HCC early recurrence within 1 year of curative hepatectomy.…”
Section: Discussionmentioning
confidence: 98%
“…It has been revealed that global enhancer hypomethylation occurs in human HCCs, 39 which may attenuate the inhibiting effect of MBD2 on functional oncogenes. Systemic inflammation is an important indicator for unfavorable postoperative prognosis in HCC 40 . MBD2 mediates epigenetic transcriptional silencing by binding to methylated DNA, thus playing an important role in preventing tumor‐promoting inflammation 41 .…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the recent research by Dai et al ( 1 ) entitled “ Nomograms based on clinicopathological factors and inflammatory indicators for prediction of early and late recurrence of hepatocellular carcinoma after surgical resection for patients with chronic hepatitis B ”.…”
mentioning
confidence: 99%